Use of beef-semen on dairy cows: breeding strategies, economics of using beef embryo on Jersey dairy cows and association of transfer of passive immunity with morbidity and mortality in dairy-beef crossbred calves - Pereira, Jéssica Marcela Vieira (2022)
This thesis was developed from three studies. The objectives of the first study were to describe the current management practices on the use of beef semen (BS) by dairy farms; and to determine factors associated with the price of day-old dairy-beef crossbred calves. In January 2020, we mailed a printed version of the beef semen use survey to dairy producers in California. The questionnaire consisted in: general herd information (n = 10), BS (n = 17), and sexed dairy semen (n = 6) management. Most dairies (81%) reported using BS on dairy cows, starting (58%) using BS in the past three years. Reproductive performance was an important criterion to select cows to receive BS, and 45% of the respondents reported starting breeding cows with BS from the third breeding on. The region of California, contract with a calf ranch, and the herd breed explained 76.7% of the observed variation in the day-old dairy beef crossbred calf price. Survey results demonstrated the main breeding strategies adopted by dairy farmers. The objectives of the second study were, to evaluate the economic feasibility of using beef in vitro produced embryo transfer (IVP-ET) in Jersey herds, and to evaluate the economic feasibility of retaining the ownership of Jersey-beef crossbred calves and pure-beef calves. A Markov chain model was developed to evaluate different scenarios of using BS and IVP-ET. We varied the IVP-ET cost ($85 or $170), the pure beef calf price ($200 or $300), and by marketing Jersey-beef and pure beef animals with one-day-old or raising them to 180 kg. A total of 8 scenarios were simulated. When the beef IVP-ET cost was $170 (scenario 4), the lowest profit ($62.1/lactating cow per year) was achieved. The highest profit was achieved for the scenario 6 raising the Jersey-beef crossbreds ($273.6). The adoption of beef IVP-ET in a reproductive program has the potential to increase herd profitability and raising the Jersey-beef crossbred calves may be a profitable strategy. The third study aimed to describe the association of failure of transfer of passive immunity (TPI) with morbidity, mortality, and ADG in dairy-beef crossbred calves. A total of 1058 dairy-beef crossbred calves were enrolled upon arrival at a calf-raising facility in California from January to August 2021. Blood was collected at 24 h post-arrival to evaluate serum IgG concentration, serum total protein. Morbidity and mortality information were recorded until 60d of life. Calves’ breeds were Holstein × Beef (49.5%), Jersey × Beef (50.6%). Prevalence of failure of TPI was 14.7% (n = 155). Overall morbidity and mortality were 84.9% (n = 898) and 2.6% (n =27). Animals with IgG ≥25.0 g/L had a lower percentage of morbidity. IgG levels <10.0 g/L were associated with decreased ADG by 0.12 kg/d. Keywords: Beef on dairy, beef semen, dairy-beef crossbred calves, reproductive strategies, transfer of passive immunity.